The Effect of Financing Margin, Religiosity, and Family on the Decision to Financing BSI Pensiunan Berkah at Bank Syariah Indonesia KC. Padangsidimpuan - Rahul Al Fatah Suripto; Marliyah Marliyah; Nur Ahmadi Bi Rahmani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study was to determine the effect of financing margin on customer decisions to finance BSI Pensiun Berkah. To determine the effect of religiosity on customer decisions to finance BSI Pensiun Berkah. To determine the influence of family on customer decisions to finance BSI Pensiun Berkah. To determine the effect of financing margin, religiosity, and family simultaneously on customer decisions to finance BSI Pensiun Berkah. In this study, the population used was pre-retired civil servant customers in Padangsidimpuan whose number was not known for certain. The research sample is part of the number and characteristics of the population. Because the researcher does not know for sure the number of pre-retirement customer populations who finance at BSI KC Padangsidimpuan, the researcher used the Lemeshow formula. So in this study, the researcher used a minimum sample size of 96 respondents who had financed at Bank Syariah Indonesia KC. Padangsidimpuan. This research method uses an associative approach and the research method used is quantitative which is based on the philosophy of positivism and uses the assistance of the IBM SPSS version 24 application program. This study used a questionnaire with a sample of 96 respondents. The results of the study indicate that financing margin, religiosity, and family simultaneously influence the customer's decision to finance a blessed pension at Bank Syariah Indonesia Kc. Padangsidimpuan, as with the results of the F-Test. Based on the results of the T-Test, the financing margin variable obtained 0.632, then the religiosity variable obtained 1.986 and the family variable obtained 4.478. So it can be concluded that only the family variable has a significant positive effect on the customer's decision to finance a blessed pension at Bank Syariah Indonesia Kc. Padangsidimpuan, because of the three variables, only the family variable obtained a value greater than the T-table of 1.986.